Cost Reduction of Electric Oven Machine Using Design for Manufacture and Assembly (DFMA) - Mahazis, Mahathir; Nawawi, Azli (Progress in Engineering Application and Technology, 2021)
Every industry needs to manufacture low cost, high quality and quicker time on the market. Design for Manufacturing and Assembly (DFMA) is a methodology that can be used to reduce or redesign many products in the manufacturing sector. The benefit of DFMA is that it can reduce the manufacture cost. The major purpose of this study is to propose a new design of electric oven. Besides that, the manufacture cost, assembly time and design efficiency are analyzing in order to support the modifications. The analyses were carried out by disassembling the electric oven, the operation of each component and 3D modeling using SolidWork software and, lastly, the DFMA design guidelines are used to create a new design. The selection criteria for a successful design are based on the cost of manufacture and the time of assembly. Finally, the design chosen has been proven to meet all the relevant requirements by improving in the operation cost, operation time and design efficiency. The existing product design efficiency is 32% and the new design is 44%. The operation time for new design also improving from 123.53s per unit to 89.08s per unit. In this study, the overall operation cost reduction is RM13.77 per unit which is RM49.39 reduce to RM35.62, the percentage reduction is 27.88%.